STUDI PEMBUATAN KERAMIK BERPORI BERBASIS CLAY DAN KAOLIN ALAM DENGAN ADITIF ABU SEKAM PADI - Siagian, Henok; Hutabalian, Martha (JURNAL PENELITIAN SAINTIKA, 2012)
This research aims to make clay and Pahae natural kaolin based porousceramic using hull of rice ash as additive and tu study the influence of variation ofcomposition of hull of rice additive with clay and Pahae natural kaolin to the characteristics of porous ceramic on sintering temperature 9ooac, 10ooac, and11000C. The raw material of this ceramic consists of clay and Pahae kaolin mixing with theaddition of hull of rice ash as additive in the percentage 0%, 5%, 10% and 15% andthen sintering of each admixture in temperature of 9000C, 1000°C and 1100°C. Thisaims to get the better admixture by burning and to study whether is there anincreasing of physical characteristics of the porous ceramic material, i.e. burningwastage, porosity, density, hardness and XRD (X-Ray Diffraction) analysis. Based on the results of research indicates that the physical characteristics of clay andPahae natural kaolin based porous ceramic with hull of rice ash as additive is : theburning waste on sintering temperature 900°C-11000C is (18.91 - 23.31)%, theporosity value is (27.80 - 56.94)%, density value is (1.33 - 1.71) gr!cm3, hardnessvalue is (8.78 - 12.87) kgflmm2 and the results of XRD analisys indicates that thedominant phase on ceramic is Aluminium Silicate Hydroxide [Al2Si20s(OH)4].